Identification of therapeutic targets and prognostic biomarkers among frizzled family genes in glioma - Huang, Ke; Xu, Huimei; Han, Liang; Xu, Ruiming; Xu, Zhaoqing; Xie, Yi (Frontiers in Molecular Biosciences, 2023)
(1) Background: Frizzled gene family (FZDs), as the key node of Wnt signaling pathway and mTOR signaling pathway, have not been fully elucidated in glioma. This study aims to further our understanding on the effects of FZDs in glioma, and find novel biomarkers for gliomas. (2) Methods: The RNA-seq data were downloaded from TCGA and GTEx. The survival analyses, Cox regression, nomogram, calibration curves, ROC curves, gene function enrichment analyses and immune cell infiltration analyses were carried out by R. (3) Results: High expressions of FZDs were associated with the activation of mTOR signaling. FZD1/2/3/4/5/7/8 was significantly higher expressed in tumor tissues, and the high expression of FZD1/2/5/6/7/8 was evidently associated with poorer prognosis. FZD2 and FZD6 could positively serve as independent predictors of poor prognosis. Gene function analysis showed that FZDs were associated with mTOR signaling, immune response, cytokine-cytokine receptor interaction, extracellular matrix organization, apoptosis, p53 signaling pathway. (4) Conclusions: FZD1/2/5/6/7/8 could possibly be a disadvantageous factor for treatment of glioma, meanwhile, FZD2 and FZD6 were likely to serve as novel independent predictors of poor prognosis of malignant tumor.